Enhancing Science Literacy through Development of Acid-Base E-module using Book Creator - Etik Krisnawati; Jimmy Copriadi; Maria Erna (Universitas Pendidikan Mandalika, 2023)
The aim of this study was to produce a science literacy-based e-module prototype using a book creator focused on acid-base material and to investigate user responses to the product. The Plomp model was utilized for the design of the research. The e-module was validated by two material experts and one media expert. The trial of user responses was conducted on teachers and students. The results showed that the e-module met the criteria for validity with a high average score of 97.14% for material substance and 97.27% for learning design. The media aspect received an average score of 96% for visual communication and 98.33% for software utilization. The responses of both teachers and students were positive, with average scores of 93.70% and 86.07%, respectively.